Exploring healthcare professionals adoption and use of Information and Communication Technology using Q-methodology and Models of Technology Acceptance - Ladan, Muhammad Awwal; Wharrad, Heather; Windle, Richard (2017)
Background: Information and communication technologies (ICTs) and more specifically e-health are viewed as important tools within healthcare. They are used to support clinical activities such as interactions between healthcare professionals and patients, clinical self-development, patient education, routine clinical activities, and also have the potential to address many challenges affecting healthcare sectors globally. However, there is still limited information on how technologies are adopted and used within clinical practice by health professionals particularly in countries in Sub Saharan Africa (SSA). Methodology: This study used Q-methodology and models of technology acceptance (TAM and UTUAT) to explore the factors that influence ICT adoption among nurses and physicians in clinical practice in SSA. Thirty six participants from a tertiary hospital in SSA conducted Q-sorts of 46 statements relating to their interaction with technologies in their clinical practice. Results: Four factors; the patient-driven adopters, the task-driven adopters, the pragmatists and the e-health champions emerged after Q-analysis representing the distinct views of this group of healthcare professionals. Conclusion: The findings suggest different viewpoints to the adoption and use of e-health resources in clinical practise. These views may help understand how these health professionals make their choices when it comes to ICT in health care.